Hybrid warfare division: An urgent operational requirement for India - Kumar, Narender (U.S.I Journal)
Hybrid and asymmetric warfare are an everyday war that developing countries are facing in a military and economic competitive environment. It is difficult to categorise hybrid war as military or quasi military challenge but it has elements of military and non-military domains. This article examines why Hybrid warfare is a necessity for India and therefore development of hybrid warfare capabilities is imperative because, the state may be under attack but unaware of who is attacking, what is he attacking and how is he attacking. To react to such a threat, where lines of peace and war are blurred, India must build hybrid warfare capabilities for dynamic response to ambiguous and alternative wars. The threat may be kinetic, non-kinetic, political, cyber, transnational organised crime, global terrorism, asymmetric conflict, threat to resources, to diaspora and to key infrastructure. Hybrid war cannot be fought in silos; it requires integration of all elements of hybrid war for offensive and defensive operations. Therefore, India needs to develop asymmetric edge and build capabilities to fight ambiguous and amorphous adversaries by synergised application of intelligence, information, cyber, electronic, conventional and unconventional means. For this India requires a new organisation for Hybrid War, a Hybrid warfare Division, the article brings out similar models in some countries which have gone in for it and thereafter gives a suggested organisation and capability development framework for this division. - Reproduced